Characterization of the Essential Oil in Leaves of Chimonanthus praecox var. concolor - Wu, Juan; Wu, Bi-Hua; Cao, Li; Hu, Xi-Gui; Xu, Zheng-Jun; Zheng, You-Liang (Asian Journal of Chemistry, 2011)
Wintersweet [Chimonanthus praecox (L.) Link] belonging to the Calycanthaceae family is a famous traditional fragrant flower plant with high ornamental value. The extraction conditions of hydrodistillation were optimized for the essential oil in leaves of C. praecox var. concolor using orthogonal design. The best extraction conditions were established as comminution degree of wintersweet leaves was 0.9 mm, the material-liquid ratio for 5-fold water, the maceration and distillation times for 2 h and 8.5 h, respectively. Twenty-three components in the essential oils were identified by gas chromatography-mass spectrometry (GC-MS). The main chemical compounds of the essential oil were bornyl acetate (20.98 %), caryophylene oxide (18.49 %), borneol (4.36 %), (+)-d-cadinene (4.95 %), elemol (4.24 %), juniper camphor (4.21 %) and phytol (4.29 %), which might be associated with the fragrancy.